Antidiabetic Effect of Brain-Derived Neurotrophic Factor and Its Association with Inflammation in Type 2 Diabetes Mellitus. (14th September 2017) - Eyileten, Ceren; Kaplon-Cieslicka, Agnieszka; Mirowska-Guzel, Dagmara; Malek, Lukasz; Postula, Marek
Abstract : Brain-derived neurotrophic factor (BDNF) is a neurotrophin, which plays an important role in the central nervous system, and systemic or peripheral inflammatory conditions, such as acute coronary syndrome and type 2 diabetes mellitus (T2DM). BDNF is also expressed in several nonneuronal tissues, and platelets are the major source of peripheral BDNF. Here, we reviewed the potential role of BDNF in platelet reactivity in T2DM and its association with selected inflammatory and platelet activation mediators. Besides that, we focused on adipocytokines such as leptin, resistin, and adiponectin which are considered to take part in inflammation and both lipid and glucose metabolism in diabetic patients as previous studies showed the relation between adipocytokines and BDNF. We also reviewed the evidences of the antidiabetic effect of BDNF and the association with circulating inflammatory cytokines in T2DM.